Mengenal Kutil Kelamin: Edukasi dan Pencegahan untuk Kesehatan Reproduksi di Lingkungan Kerja Kampus UNM Parangtambung - Idris, Irma Suryani; Pagarra, Halifah; Muis, Abd.; Rachmawaty, Rachmawaty; Hiola, St. Fatmah (JKM: Jurnal Kemitraan Masyarakat, 2025)
In Indonesia, the incidence of genital warts continues to increase and is the third largest disease of sexually transmitted infections. The possibility of being infected through sexual intercourse with a partner infected with HPV, either in subclinical form, is 75%. Genital HPV infection generally affects moist mucosa. Microscopic abrasion and repeated trauma can increase infectivity and replication of the virus. The incubation period of HPV is between 8 weeks to 9 months. With these concerns, there is a need for socialization or counseling regarding genital warts, education and prevention, especially in the work environment. This community service was carried out in the UNM Parangtambung Campus Work environment which aims to provide an understanding or education about the dangers of genital warts to reproductive health. The delivery of material in this training was carried out in a classical manner, all participants followed the material presented through lectures, discussions and questions and answers. This activity was attended by the cleaning service on duty at the UNM Parangtambung Campus Work Environment. The results of this community service were responded to well by the participants, the high interest and motivation of the training participants greatly supported the transfer of knowledge and skills from the resource person to the training participants. Keywords: genital warts, education, prevention, cleaning service.